Respon Pertumbuhan Dan Hasil Tanaman Pakcoy (Brassica Rapa L.) Pada Media Terkontaminasi Logam Berat Tembaga (Cu) - Amir Putra, Dipo Dwitanto; Rosyidah, Anis; Muslikah, Siti (Folium : Jurnal Ilmu Pertanian, 2024)
Heavy metal waste (Cu) is a current environmental problem. The phytoremediation method utilizes plants with a high capacity for metal accumulation to reduce concentrations of heavy metals in soil by planting heavy metal-binding plants. Pakcoy (Brassica rapa L.) as an indicator of economic viability is a cultivar that is resistant to Cu metal stress. The objective of this study is to determine the effect of heavy metal copper (Cu) on the growth and yield of pakcoy (Brassica rapa L.) as a hyperaccumulator. Then to determine the distribution of metal (Cu) in pakcoy (Brassica rapa L.) plant organs. The research was conducted experimentally using a simple Randomized Block Design. The treatments in this study involve different dosages of copper (Cu),consisting of D0= 0 mg, D1= 500 mg, D2= 625 mg, and D3= 750 mg of soil. The data obtained were analyzed using variance (F-test) and test with the least significant difference (LSD) test at the 5% level In the presence of a significant effect. The findings reveal that the level of heavy metal Cu inhibits root growth, branching, resulting in shorter plants, and decreased chlorophyll content. The higher the concentration of Cu, the lower the growth and chlorosis of plants due to metabolic disturbances. The highest accumulation of Cu metal in the roots occurred at concentrations with values of 625 mg and 750 mg. The accumulation of Cu was higher in the root tissue than in the leaf TF ranging from 0.11 to 0.17